2022
DOI: 10.3390/cancers14225598
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Arsenic Exposure and Transcriptomic Profile in Basal Cell Carcinoma

Abstract: Exposure to inorganic arsenic (As) is recognized as risk factor for basal cell carcinoma (BCC). We have followed-up 7000 adults for 6 years who were exposed to As and had manifest As skin toxicity. Of them, 1.7% developed BCC (males = 2.2%, females = 1.3%). In this study, we compared transcriptome-wide RNA sequencing data from the very first 26 BCC cases and healthy skin tissue from independent 16 individuals. Genes in “ cell carcinoma pathway”, “Hedgehog signaling pathway”, and “Notch signaling pathway” were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 59 publications
0
8
0
Order By: Relevance
“…For this study, we selected the first 32 subjects from the BEST study developing histopathologically confirmed NMSC and had the tumor tissue properly preserved in RNA later, an RNA stabilizing buffer (ThermoFisher Scientific, Waltham, MA, USA). The BEST study included 7000 men and women (m = 2840, f = 4160) who were known to be exposed to As through consuming well water containing As [ 32 , 39 ]. This study included all subjects with clinically visible non-malignant skin lesions (melanosis, leukomelanosis, or keratosis)—a known manifestation of As toxicity.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…For this study, we selected the first 32 subjects from the BEST study developing histopathologically confirmed NMSC and had the tumor tissue properly preserved in RNA later, an RNA stabilizing buffer (ThermoFisher Scientific, Waltham, MA, USA). The BEST study included 7000 men and women (m = 2840, f = 4160) who were known to be exposed to As through consuming well water containing As [ 32 , 39 ]. This study included all subjects with clinically visible non-malignant skin lesions (melanosis, leukomelanosis, or keratosis)—a known manifestation of As toxicity.…”
Section: Methodsmentioning
confidence: 99%
“…A skin biopsy was performed on a total of 727 participants (m = 417, f = 310). Among them, 37.7% of the biopsies showed BD, 2.9% had invasive SCC, 16.1% showed BCC, and the rest (43.3%) showed arsenical keratosis or other skin conditions [ 32 ]. Thus, among the As-exposed study population, 2.2% of the male and 1.3% of the female participants developed BCC, while 0.4% of the male and 0.2% of the female participants developed SCC over the six-year follow-up.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations